2018
DOI: 10.1002/mabi.201800209
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid Cross‐linked Polysaccharide‐Based Multifunctional Hemostatic Microparticles for the Regulation of Rapid Wound Healing

Abstract: Hemostatic microparticles (HMs) have been widely used in surgery. To improve the comprehensive performance of HMs, multifunctional HMs named HM15 and HM15′ are prepared from starch, carboxymethyl chitosan, hyaluronic acid, and tannic acid. Herein, tannic acid is used as an effective cross‐linker. A 3D network structure for cell growth and wound repair can be formed by secondary cross‐linking. Through synergistic effect of these natural materials, the process of wound healing can be regulated controllably. HM15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 69 publications
(81 reference statements)
0
75
0
Order By: Relevance
“…BCI is a useful index for the evaluation of blood clotting capacity of various materials. [ 30 ] In this experiment, the absorbance of free hemoglobin in the supernatant of hydrogels treated with blood was measured to compare the amount of hemoglobin incorporated in the clot formation in the presence of the hydrogel. Therefore, higher absorbance was indicative of lower blood clotting ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCI is a useful index for the evaluation of blood clotting capacity of various materials. [ 30 ] In this experiment, the absorbance of free hemoglobin in the supernatant of hydrogels treated with blood was measured to compare the amount of hemoglobin incorporated in the clot formation in the presence of the hydrogel. Therefore, higher absorbance was indicative of lower blood clotting ability.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, higher absorbance was indicative of lower blood clotting ability. [ 30 ] The results showed that GelTA and GelTA‐Alla hydrogels have higher blood clotting ability than commercially available gauzes ( Figure a). Besides, Alla loading into the hydrogels did not alter the hemostatic effect of the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8–11 ] In the previous study, we have reported several polysaccharide based hemostatic microspheres with different microscopic morphology, which had exhibited excellent performance in the applications of hemostasis, antibacterial activity, and wound healing. [ 3,12–14 ] In fact, polysaccharide based hemostatic products are available in variety of forms, such as, hydrogel, sponges, gauze, and microspheres. The purpose of the present review is to report the research progress of polysaccharide based hemostatic strategy for ultrarapid hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides, the naturally derived polymers composed of repeating sugar blocks, have attracted much attention as promising candidates for arresting haemorrhage because of their impeccable biocompatibility, biodegradability, marginal immunoreactivity, and abundance in nature . Most importantly, the ease of preparation for these biomaterials allows them to be formulated in dry powder and granular forms with microporous structures to enlarge the blood absorption efficiency of haemostatic powders . In the recent decade, prominent products such as TraumaDex (microporous polysaccharide haemospheres obtained from potato starch) and Celox (CX) (chitosan‐based granules and flakes) have gained Food and Drug Administration (FDA) approval and revealed comparable efficiency in terms of haemostatic capacity and survival rate to the mineral‐based powders (QuikClot and Woundstat) .…”
Section: Introductionmentioning
confidence: 99%
“…6,19,20 Most importantly, the ease of preparation for these biomaterials allows them to be formulated in dry powder and granular forms with microporous structures to enlarge the blood absorption efficiency of haemostatic powders. 12,21,22 In the recent decade, 5,23 Despite the reduced immunogenicity of the polysaccharide-based powders, several in vivo results demonstrated that mild to severe inflammatory responses at the surrounding tissues could be detected because of the presence of residual powders in the wound. 24,25 Therefore, the recommended procedures to attenuate the foreign body reactions are reducing the amount of haemostatic powders while administration, followed by exhaustive removal of the powders from wounds upon acquiring haemostasis.…”
mentioning
confidence: 99%